Pengaruh Influencer Marketing, Marketing Content dan Viral Marketing Campaign Terhadap Niat Membeli Produk Makanan dan Minuman Di Kalangan Generasi Z - Rahmadina Azzahhra, A. Malika; Auliya Sari, Masyita; Karmelia, Sutra; Welson, Troy; Erwin, Erwin (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The rapid development of social media has generated significant changes in consumer behavior, particularly among the digital generation that increasingly relies on online content as the basis for decision-making. However, micro, small, and medium enterprises (MSMEs) in the food and beverage sector still face challenges in building consumer trust, capturing audience attention, and increasing purchase intention through digital marketing strategies. This study examines how influencer marketing, marketing content, and viral marketing contribute to enhancing consumer purchase intention. This descriptive quantitative study involved 178 active social media users who had been exposed to influencer content, viral campaigns, and digital marketing materials. Data were collected through a five-point Likert scale questionnaire and analyzed using PLS-SEM with the support of SmartPLS version 4.0.The findings indicate that influencer marketing has a positive significant effect on purchase intention. Marketing content shows a positive and significant influence on purchase intention, emphasizing that the effectiveness of digital marketing is not solely determined by visual appeal but is strongly shaped by the informativeness, creativity, and relevance of the message. Additionally, viral marketing also exerts a positive and significant impact on purchase intention, particularly through the rapid and extensive spread of promotional messages. Overall, these results highlight the importance of content quality and audience engagement dynamics in transforming digital marketing strategies into tangible boosts in consumer purchase intention.